TRIS(PYRAZOLYL)BORATE COMPLEXES OF 3-METHOXY-3-OXOPROPYLTIN(IV) - CRYSTAL-STRUCTURE AND PROPERTIES OF CH3OOCCH2CH2SN((PZ)3BH)X2 (X = CL, NCS) - JUNG, OS; JEONG, JH; SOHN, YS (ELSEVIER SCIENCE SA LAUSANNE, 1990)
(Hydrotris(pyrazolyl)borato)(3-methoxy-3-oxopropyl)tin(IV) compounds, CH3OOCCH2CH2Sn((pz)3BH)X2 (1:X = Cl; 2: X = NCS), have been prepared and examined. The X-ray crystal structures of 1.CH2Cl2 (C2/c; a 20.658(4), b8.848(1), c26.485(5) angstrom, beta-109.73(1)-degrees; Z = 8; R = 0.540) and 2.C6H6 IP1BAR; a 9.756(10, b 11.783(1), c 13.407(1) angstrom, alpha-110.236(9), beta-109.647(8), gamma-95.842(8)-degrees; Z = 2; R = 0.0463) shows discrete molecules containing a distorted octahedral tin atom, and a facial tridentate hydrotris(pyrazolyl)borate ligand; the carbonyl oxygen atom of 3-methoxy-3-oxopropyl group is released from the tin atom to accommodate the negative tridentate ligand. The spectral and the cryoscopic data for solid state or in solution are consistent with the crystal structures.
Keywords: SN-119 CHEMICAL-SHIFTS; MOLECULAR-STRUCTURE; DIMETHYLTIN DIISOTHIOCYANATE; COORDINATION CHEMISTRY; 7-COORDINATE ORGANOTIN; RAY STRUCTURE; NMR-SPECTRA; LIGANDS; 5-COORDINATE; DERIVATIVES